Modern Risk Management Methods in Agricultural Companies - Yulia Y. GOLUBYATNIKOVA (Communications of International Proceedings, 2021)
Considering the ongoing processes in domestic agriculture, its constant transformation should be noted. Under these conditions, an entrepreneur has to make a decision every second in his business activity. The most difficult problem is assessing the potential consequences of risks, i.e. amounts to cover unforeseen expenses. To solve it, it is necessary to apply risk management methods. In conditions of uncertainty and increasing competition, the tasks of reducing risks and increasing the efficiency of companies’ activities come to the fore. To solve them, analysts, consultants, risk managers and administrators are constantly looking for ways and find new conceptual approaches, organizational forms and methods of company management. The article considered modern approaches to improving the efficiency of enterprise management, such as the organization of a risk management service; organization of a virtual enterprise; creative concept of its development; motivation for effective risk management; the formation of consulting services for various forms of organization of agricultural enterprises; legal regulation of entrepreneurial activity.
Keywords: Risk; Risk Management System; Risk Management Methods; Modern Management Methods.